Computer aided analysis of ball burnishing process - Storozh, Y.; Lyutak, I.; Storozh, B.; Vasylyk, O.; Yatsyshyn, M.; Pasyeka, M. (Управляющие системы и машины, 2015)
The finite element model analysis of a rigid sphere indentation into a half-space is created and investigated as a part of comprehensive study of a ball burnishing process. The model shows good fidelity of the material elastic behavior by the Hertz contact theory. The elasticplastic behavior of the material with a power dependence of the isotropic strain strengthening is studied. Parameters for the further ball burnishing research are recommended. В межах аналізу процесів обкочування кулькою створено і досліджено скінченно-елементну модель вдавлювання жорсткої сфери в півпростір. Модель свідчить про високу точність відтворення пружної поведінки матеріалу за теорією Герца. Вивчено пружно-пластичну поведінку матеріалу зі степеневою залежністю ізотропного деформаційного зміцнення. Обґрунтовано рекомендації щодо вибору параметрів дослідження процесу обкочування кульками. В рамках анализа процессов обкатывания шариком создана и исследована конечно-элементная модель вдавливания жесткой сферы в полупространство. Модель свидетельствует о высокой точности воспроизведения упругости материала по теории Герца. Изучено упруго-пластичное поведение материала со степенной зависимостью изотропного деформационного усиления. Обоснованы рекомендации выбора параметров исследования процесса обкатывания шариком.